Socialization of self-care guidelines for tuberculosis patients at UPT Pulmonary Health Services in West Kalimantan Province - Tri Wahyuni; Parliani Parliani; Tutur Kardiatun; Prasetyo Aji Nugroho; Al Fikri; Muamar Muamar; Muhammad Riduan; Veni Fitrianingsih (Universitas Muhammadiyah Magelang, 2021)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis, which can harm the lungs and attack other organs. This will result in nursing issues, the risk of infection spreading to other organs and people, ineffective airway clearance, impaired gas exchange, nutritional disorders, and psychosocial problems. Efforts are made to overcome nursing problems by increasing the participation of patients and families, who serve as the primary supporters. The intervention performed by the patient as an agent for himself is known as self-care. Self-care is concerned with an individual's ability to care for and maintain his or her own health. Treatment, family support, and nutritional fulfillment are all part of TB treatment. The outcomes of service activity at UPT Pulmonary Health Services includes teaching health workers about self-care for TB patients, as well as conducting follow-up discussions about TB patients with anxiety in the intensive phase.